Potensi Susu Basi menjadi Pupuk Organik dengan Penambahan Larutan Effective Microorganism 4 dan Cocopeat - Triwuri, Nurlinda Ayu; Dwityaningsih, Rosita; Handayani, Murni (Universitas Diponegoro, 2019)
During this time, the remaining milk that has been consumed only wasted. Milk content is strongly associated with nutrients to increase crop productivity. This requires innovations in the manufacture of organic fertilizer products. The purpose of this study was to determine the best composition comparison between stale milk, EM4 solution and cocopeat in the process of making liquid and solid organic fertilizer and determine the c-organic value, Ntotal, P2O5total, K2Ototal, and pH value. Initial analysis of liquid organic fertilizer obtained pH values of 5.10, P2O5total Â of 0.342% and Ntotal of 0.569% at initial control (stale milk only) and final values of 1.010% ofÂ P2O5total, 1.113% of Ntotal and 10.480% of organic carbon in R3 ( 30: 5: 1). Initial analysis of solid organic fertilizer obtained pH values 5.26%, 2.668% P2O5total, 0.952% K2Ototal and 2.780% Ntotal at R1 (10: 5: 1) and final values obtained 1.578% P2O5total at R1 (10: 5: 1) , 2.937% Ntotal in R2 and 43.912% carbon organic in R3. This shows that stale milk with the addition of EM4 and cocopeat solutions has an effect on phosphorus and nitrogen nutrients in liquid and solid organic fertilizer.